Restoring the Entrails of Welfare Reform. Issue 2 (June 2017) - Parolin, Zachary; Wiseman, Michael
Abstract : The Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) of 1996 famously "ended welfare as we [knew] it" by replacing the state‐operated Aid to Families with Dependent Children (AFDC) program with a revised funding scheme called Temporary Assistance for Needy Families (TANF). In the summer of 2012, controversy erupted over a memorandum issued by the U.S. Department of Health and Human Services (HHS), Administration for Children and Families (ACF), concerning state options for TANF performance reporting. Opponents of the Obama administration claimed the policy initiative specified in the memorandum signaled a fundamental change in direction of the national welfare policy established by PRWORA—that it "gutted" welfare reform. The memorandum has not (as of 2016) been rescinded, and the issues raised in the ensuing controversy remain unresolved. We review the controversy. We argue that while there is some justification in criticism of the Obama administration's strategy, the initiative addressed an important problem: the inadequacy of the program's performance measure given the variation in resources available to states in meeting the program's goals. The ACF memo was in our judgment a responsible step toward finding methods for improving TANF performance and, as conducted, the guts debate retarded this search.